A prospective large-scale study of methods for the detection of latent Mycobacterium tuberculosis infection in refugee children. Issue 5 (30th April 2010) - Lucas, Michaela; Nicol, Pam; McKinnon, Elizabeth; Whidborne, Rebecca; Lucas, Andrew; Thambiran, Aesen; Burgner, David; Waring, Justin; French, Martyn
Abstract : Background: Diagnosis of latent tuberculosis infection (LTBI) is a cornerstone of the health assessment of resettled high incidence populations, particularly in children. Two blood-based interferon γ release assays (IGRAs), T-SPOT. TB and QFT-Gold in-tube (QFT-GIT), have greater sensitivity and specificity than the tuberculin skin test (TST), but their performance as screening tools for LTBI in children, especially refugee children, remains unclear. Methods: 524 African and ethnic Burmese children, including 107 under 3 years of age, were prospectively enrolled in a comparison of the T-SPOT. TB and QFT-GIT. The TST was also performed in 342 of the children. Results: The T-SPOT. TB and QFT-GIT had similar rates of positivity (8% and 10%, respectively) and showed good concordance when both tests gave definitive results (κ=0.78; p<0.0001). However, the IGRAs had significant failure rates: 15% of QFT-GIT gave indeterminate results due to failed mitogen response and 14% of T-SPOT. TB results were inconclusive, largely because of insufficient mononuclear leucocyte yields. Failure of the QFT-GIT mitogen response was associated with African ethnicity and co-morbid infections, particularly with helminths. The TST results showed poor concordance (∼50%) with both IGRAs. Conclusions: It is reasonable to screen using either IGRA with follow-up by the alternative if the test fails. In general, the QFT-GIT is the preferred option for non-African populations but the T-SPOT. TB is recommended when there are epidemiological and/or clinical high risk factors for TB infection. However, both IGRAs have methodological and performance characteristics that limit their usefulness in refugee children, highlighting the need for continued development of screening strategies.